Is it safe to proceed with heart transplant in a patient with active tuberculosis? Strategies and challenges based on a case report - Laura Hastenteufel; Marcelo Basso Gazzana; Nadine Clausell; Lívia Adams Goldraich, MD (JHLT Open)
Transplant candidates are at increased risk of developing active tuberculosis (TB), and its diagnosis and treatment may be especially challenging. Although screening and treatment for TB are recommended in heart transplant candidates, there is lack of evidence on how to manage active TB infection in this scenario. Herein, we report challenges of performing a heart transplant in a 69-year-old patient with progressive heart failure and active, symptomatic TB infection. We aimed to emphasize the importance of proper screening of TB in solid organ transplant candidates, as well as to suggest that, in selected patients, it may be safe to proceed with transplant after an initial period of treatment with antituberculous agents.